Discovery of potential drugs for human-infecting H7N9 virus containing R294K mutation - He JY; Li C; Wu G (Dove Medical Press, 2014)
Jiao-Yu He,1,* Cheng Li,2,* Guo Wu3 1College of Life Sciences and Key Laboratory for Bio-resources of Ministry of Education, Sichuan University, 2College of Agronomy, Sichuan Agricultural University, 3College of Life Sciences, Sichuan Normal University, Chengdu, People’s Republic of China *These authors contributed equally to this work Background: After the first epidemic wave from February through May 2013, the influenza A (H7N9) virus emerged and has followed a second epidemic wave since June 2013. As of June 27, 2014, the outbreak of H7N9 had caused 450 confirmed cases of human infection, with 165 deaths included. The case-fatality rate of all confirmed cases is about 36%, making the H7N9 virus a significant threat to people’s health. At present, neuraminidase inhibitors are the only licensed antiviral medications available to treat H7N9 infections in humans. Oseltamivir is the most commonly used inhibitor, and it is also a front-line drug for the threatening H7N9. Unfortunately, it has been reported that patients treated with oseltamivir can induce R294K (Arg294Lys) substitution in the H7N9 virus, which is a rare mutation and can reduce the antiviral efficacy of inhibitors. Even worse, deaths caused by such mutation after oseltamivir treatment have already been reported, indicating that the need to find substitutive neuraminidase inhibitors for currently available drugs to treat drug-resistant H7N9 is really pressing.Materials and methods: First, the structure of H7N9 containing the R294K substitution was downloaded from the Protein Data Bank, and structural information of approved drugs was downloaded from the ZINC (ZINC Is Not Commercial) database. Taking oseltamivir carboxylate as a reference drug, we then filtered these molecules through virtual screening to find out potential inhibitors targeting the mutated H7N9 virus. For further evaluation, we carried out a 14 ns molecular dynamic simulation for each H7N9–drug complex and calculated the binding energy for each candidate drug.Results: We found five inhibitors that could be candidate drugs for treating the mutated H7N9 virus. Docking poses showed these drugs could bind to the virus effectively, with the contribution of hydrogen bonds and hydrophobic interactions. With regard to the molecular dynamic simulations, receptor–ligand complexes formed by these candidate drugs were more stable than the one formed by oseltamivir carboxylate. The binding energy of oseltamivir carboxylate was -122.4 kJ/mol, while those for these potential inhibitors were -417.5, -404.7, -372.2, -304.3, and -289.9 kJ/mol, much better than the reference drug.Conclusion: Given the current and future threat of the mutated H7N9 virus, it is urgent that potent drugs and effective antiviral therapeutics be found. Our study therefore is able to complement currently available drugs for influenza A infectors and helps to prevent the ongoing threat of H7N9 virus. Keywords: H7N9, neuraminidase, mutation, virtual screening, inhibitor